From Competency to Itqan: Integrating Prophetic Spiritual Excellence into the Learning Outcomes of the Merdeka Curriculum - Faqih Abdul Aziz; Rohmat Robi' Rozaqiy; Albert Taqy Asy Syakur; Akbar Yusgiantara; Ahmad Yusam Thobroni (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The integration of Outcome-Based Education (OBE) within Indonesia’s Merdeka Curriculum encounters philosophical friction, as mechanistic competency standards frequently marginalize spiritual values. This study aims to reconstruct OBE’s philosophical foundation by synthesizing Prophetic Traditions into a holistic instructional design model. Employing a qualitative library method alongside a hermeneutic synthesis approach, this research systematically analyzes five canonical Hadiths to establish a robust